'Who's Afraid of ISIS?' Security doxa and the doxa of insecurity. Issue 1 (2nd January 2018) - Monk, Daniel Bertrand
ABSTRACT: In theories of praxis, doxa are commonly understood as predispositives to judgment. They cannot be apprehended directly but must be derived from the insufficiencies of the most commonplace assertions and the most transparently typified reactions to them. As the uncontested predicates of further contention, doxa are far from epiphenomal to the concerns of any critical studies on security, as the essays in this collection seek to elucidate. The studies assembled here advance towards a doxological understanding of contemporary conflict, in particular, by reviewing the unreflexive pairing of a revisionist political movement and the phenomenon of fear. More specifically, these essays seek to excavate the commonplace and uncontested association of ISIS with fear. In a universe of threats that are no less brutal or horrifying than ISIS, but which the current attention economy fails to pair with fear, the case of the Islamic State provides students of conflict with an opportunity to assess the system of pre-predicative judgments necessary to identify contemporary threat imaginaries to begin with.